Prevalence and clinical significance of anti-neutrophil cytoplasmic antibodies in rheumatoid arthritis-associated interstitial lung disease - Zhe Huang; Tingting Wu; Rongdan Lu; Haijun Zhou; Yun Zhang; Li Huang; Yongxiong Gan; Hequn He (BMC Pulmonary Medicine)
Abstract Background Patients with rheumatoid arthritis (RA) or rheumatoid arthritis-associated interstitial lung disease (RA-ILD) are commonly positive for antineutrophil cytoplasmic antibodies (ANCAs). The causal relationship between RA-ILD and ANCAs and the role of ANCAs in RA-ILD remain unclear. The purpose of this study was to estimate the prevalence of ANCAs in RA-ILD patients and to investigate the clinical characteristics and outcomes of ANCA-positive RA-ILD patients. Methods Data from 104 RA-ILD patients with available ANCA results at our centre from March 2010 to June 2024 were retrospectively reviewed. ANCA positivity was defined as the presence of any one or a combination of perinuclear ANCAs (P-ANCAs), cytoplasmic ANCAs (C-ANCAs), anti-MPO or anti-PR-3. Clinical data from each patient’s initial diagnosis were collected and analysed. The clinical characteristics and survival of the ANCA-positive and ANCA-negative RA-ILD groups were compared. Results Thirty-three out of the 104 (31.7%) RA-ILD patients were positive for ANCAs. The percentages of patients positive for P-ANCAs, MPO-ANCAs, C-ANCAs, and PR3-ANCAs were 27.9% (29/104), 1.9% (2/104), 1.9% (2/104), and 1.0% (1/104), respectively. Compared with ANCA-negative RA-ILD patients, a greater proportion of ANCA-positive RA-ILD patients had respiratory symptoms, serum autoantibody (ANA) positivity, poorer baseline pulmonary function, and acute exacerbations of ILD (AE-ILD). The usual interstitial pneumonia (UIP) pattern (57.6%) was the most common chest high-resolution computed tomography (HRCT) pattern observed. ANCA-positive RA-ILD patients were more likely to have traction bronchiectasis (P = 0.029), honeycombing (P < 0.001), and oddly shaped cysts (P = 0.020) than were ANCA-negative RA-ILD patients. Univariate Cox analysis revealed that P-ANCA positivity [hazard ratio (HR) = 2.24, 95% confidence interval (CI): 0.91–5.52; P = 0.046] is a trend of survival association in RA-ILD, but this was not confirmed in the multivariate analysis. Multivariate Cox analyses revealed that a history of smoking (HR = 2.53, 95% CI: 1.10–5.83; P = 0.030) and a systolic pulmonary artery pressure (SPAP) ≥ 37 mmHg (HR = 10.24, 95% CI: 4.07–25.77; P < 0.001) were independently associated with shorter survival in RA-ILD patients. Conclusions The prevalence of ANCAs in patients with RA-ILD is high, and ANCA testing could be considered in the diagnostic workup for RA-ILD. Oddly shaped cysts with or without a UIP pattern may be a characteristic chest imaging manifestation of ANCA-positive RA-ILD. More attention should be given to RA-ILD patients who have elevated SPAP.